Estimasi Produksi Sumber Daya Alam (Produk Tambang) dan Tingkat Kelulusan Sekolah Serta Jumlah Tenaga Kerja Terhadap Pertumbuhan Ekonomi di Indonesia (Studi Kasus Propinsi) - Frances Roi Seston Tampubolon (Jurnal Teknologi Informatika dan Komputer, 2019)
This research is about estimating the influence of naturalresources and school graduation rates and the number ofworkers on economic growth in Indonesia. The model usedis multiple linear regression with one dependent variable andfour independent variables. The method used is the OLS(Ordinary Least Square) method, where the estimatedparameters of the models are verified by statistical tests. Thevariables used in this study include the length of time forschool graduation, the number of labor (labor), miningproducts, and PMTDB (formation of gross domestic fixedcapital). The results of data processing show that naturalresources (mining products) have a positive contribution toIndonesia's economic growth. From the last analysis that theschool graduation rate also has a positive relationship toeconomic growth.